High-throughput identification of antigen-specific TCRs by TCR gene capture - Linnemann, Carsten; Heemskerk, Bianca; Kvistborg, Pia; Kluin, Roelof J C; Bolotin, Dmitriy A; Chen, Xiaojing; Bresser, Kaspar; Nieuwland, Marja; Schotte, Remko; Michels, Samira; Gomez-Eerland, Raquel; Jahn, Lorenz; et al. (Nature medicine, 2013)
The lack of robust and high-throughput technologies to analyze the human TCR repertoire has been a bottleneck in the analysis of human T cell responses. Linnemann and colleagues have addressed this issue by using a TCR gene capture technology that, because of its quantitative nature, allows the rapid identification of TCRab pairs from bulk populations of cells without the need for single-cell cloning. Such an approach should be useful in obtaining defined antigen-reactive TCRs for therapeutic purposes. The transfer of T cell receptor (TCR) genes into patient T cells is a promising approach for the treatment of both viral infections and cancer. Although efficient methods exist to identify antibodies for the treatment of these diseases, comparable strategies to identify TCRs have been lacking. We have developed a high-throughput DNA-based strategy to identify TCR sequences by the capture and sequencing of genomic DNA fragments encoding the TCR genes. We establish the value of this approach by assembling a large library of cancer germline tumor antigen–reactive TCRs. Furthermore, by exploiting the quantitative nature of TCR gene capture, we show the feasibility of identifying antigen-specific TCRs in oligoclonal T cell populations from either human material or TCR-humanized mice. Finally, we demonstrate the ability to identify tumor-reactive TCRs within intratumoral T cell subsets without knowledge of antigen specificities, which may be the first step toward the development of autologous TCR gene therapy to target patient-specific neoantigens in human cancer.